PENGARUH DISIPLIN KERJA, KOMPETENSI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA - Yumhi Yumhi (Universitas La Tansa Mashiro, 2021)
This study aims to obtain information related to the possibility of whether performance is influenced by work discipline, competence and work motivation. Using a causal study through a survey of Bappeda employees of Lebak Regency, Indonesia, for a sample of 40 employees, data for each variable was collected separately by respondents who filled out a questionnaire. The method used in this research is quantitative survey method, while the analysis technique used is path analysis using correlation and regression.The results prove that there is an effect of work discipline on job satisfaction, there is an influence of competence on job satisfaction, there is an influence of work motivation on job satisfaction, and there is an influence of work discipline, competence and work motivation together on job satisfaction.These findings indicate that organizations need to consider the variables of work discipline, competence, and work motivation in planning and developing human resources at Bappeda Lebak Regency.